Clinical Characteristics and Survival Analysis of Patients with Supraclavicular Fossa Lymphadenopathy - Yi-Jou Kao; Wan-Lun Hsu; Yong-Chen Chen; Wu-Chia Lo; Ping-Chia Cheng; Li-Jen Liao (Diagnostics)
Background: Supraclavicular lymph nodes (SCLNs) are often indicative of malignancy, but the effectiveness of ultrasound (US) and hematological parameters in their assessment and the prognosis of patients with malignant SCLNs need further study. Methods: We retrospectively reviewed 348 patients with SCLNs from July 2007 to June 2023, including patients over 18 years of age who underwent fine needle aspiration (FNA) or core needle biopsy (CNB). Our analysis focused on clinical characteristics, US features and hematological parameters to differentiate between benign and malignant SCLNs and to assess their prognostic value, especially in the Asian population. Results: The malignancy rate was 49%, with lung cancer (22%) and lymphoma (16%) being the most common. The malignant nodes were larger and had a greater short-to-long axis ratio, irregular margins, and abnormal vascular patterns (p < 0.01). The 5-year survival rate for patients with malignant SCLNs was 40%. Blood markers, such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune–inflammation index (SII) (SII ≥ 970), were significant prognostic factors for overall survival (OS). Compared with lymphoma patients, patients with malignancies of supraclavicular and infraclavicular origins had significantly worse OS. Conclusions: Our findings highlight the importance of ultrasound in evaluating SCLNs. Furthermore, hematological markers (NLR, PLR, and SII) and the origin of SCLNs have important prognostic value.